(untitled) (Journal of Nobel Medical College, 2015)
Introduction: Hepatitis C virus (HCV) infection is a major public health challenge. It is a major cause for cirrhosis and hepatocellular carcinoma worldwide. Both the genotype and viral load of HCV determine the choice of therapy as well as outcome of therapy. The aim of this study was to evaluate clinical, biochemical and virological profile and association of HCV genotypes with viral load and liver biochemical profile. Material and Methods: This was descriptive observational study of chronic HCV infected patients who attended at the outpatient clinic of Department of Gastroenterology of TUTH, IOM from April 2013 to November 2014. During this study period 38 patients with chronic HCV infection were analyzed. Clinical profile, possible risk factors for transmission of HCV infection and liver biochemical profile were recorded. Virological profile included HCV viral load and HCV genotypes. Results: Out of 38 patients 34(89.5%) were male and 4(10.5%) were female. Injection drug use (IDU) was the most common mode for acquisition of HCV infection (55.3%). Genotype 3 was found in 21(55.26%) patients and genotype 1 was found in 17(44.74%) patients. There was no significant association between HCV genotypes and serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) level. And also there was no significant association between HCV viral load and different HCV genotypes. Conclusions: In our study HCV genotype 3 was the most prevalent genotype in patients with chronic HCV infection. Injection drug use was identified as most common identifiable risk factor for transmission of HCV infection. There was no significant association between different HCV genotypes and serum ALT, AST level and HCV viral load. Journal of Nobel College of Medicine Vol.4(1) 2015: 32-35